Determinan Non-Performing Loans Pada Sub-Sektor Bank di Bursa Efek Indonesia - Muhamad Umar Mai (Program Studi Akuntansi FPEB UPI, 2022)
This study examines the relationship between corporate governance, macroeconomic factors, and bank-specific factors and the NPL ratio using the sample of all banking sectors listed on the Indonesia Stock Exchange during the period of 2010 to 2019. The data analyzing method used Structural Equation Modeling which was processed by Warp PLS application. The results show that corporate governance measured by board size has a significant positive impact on the NPL ratio while board independence and female board of directors have a significant negative impact on it. However, this study cannot prove the significant relationship between institutional ownership and the NPL. Next, the macroeconomic factors measured by the unemployment rate have a significant positive impact on the NPL. However, again this study cannot prove the significant relationship between GDP growth and inflation rate and the NPL. Then, bank-specific factors measured by bank size and return on equity show a significant negative impact on the NPL ratio while inefficiency has a significant positive impact on it.